2018
DOI: 10.3390/ijms19124056
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Jak/STAT Signaling: Regulation and Relevance in Human Cancer and Metastasis

Abstract: Over the past three-decades, Janus kinase (Jak) and signal transducer and activator of transcription (STAT) signaling has emerged as a paradigm to understand the involvement of signal transduction in development and disease pathology. At the molecular level, cytokines and interleukins steer Jak/STAT signaling to transcriptional regulation of target genes, which are involved in cell differentiation, migration, and proliferation. Jak/STAT signaling is involved in various types of blood cell disorders and cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 297 publications
(336 reference statements)
1
57
0
Order By: Relevance
“…[25][26][27]41 The JAK/STAT signalling pathway is a crucial pathway that involves in tumour cell To compare whether there is a significant difference, same letters marked were considered to have no significant difference between the two groups and different letters marked were considered to have significant difference between the two groups differentiation, migration and proliferation and promotes cell motility by regulating actin dynamics and activating key metastasis-promoting genes. 42,43 In particular, STAT3 activation induced by interleukin family of cytokines can promote migration and invasion via the regulation of downstream target molecules such as Vimentin, Twist, MMP-9 and MMP-7. 44 Chang Q et al found that the autocrine/paracrine IL-6/JAK/STAT3 feed-forward loop has been implicated as a key player of tumour progression and metastasis and an increased level of IL-6 was found in the invasive breast tumours, with its level positively correlated with advanced stage, confirming a pivotal role of IL-6 signalling in breast tumour metastasis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27]41 The JAK/STAT signalling pathway is a crucial pathway that involves in tumour cell To compare whether there is a significant difference, same letters marked were considered to have no significant difference between the two groups and different letters marked were considered to have significant difference between the two groups differentiation, migration and proliferation and promotes cell motility by regulating actin dynamics and activating key metastasis-promoting genes. 42,43 In particular, STAT3 activation induced by interleukin family of cytokines can promote migration and invasion via the regulation of downstream target molecules such as Vimentin, Twist, MMP-9 and MMP-7. 44 Chang Q et al found that the autocrine/paracrine IL-6/JAK/STAT3 feed-forward loop has been implicated as a key player of tumour progression and metastasis and an increased level of IL-6 was found in the invasive breast tumours, with its level positively correlated with advanced stage, confirming a pivotal role of IL-6 signalling in breast tumour metastasis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The key negative regulators include the protein inhibitors of activated STATs (PIASs), SOCS, and protein tyrosine phosphatases (PTPs). In addition to these, other notable negative regulators of JAK/STAT signaling in Drosophila include the Eye transformer (ET), Ken and barbie (Ken), Enhancer of Bithorax (E (Bx)), and Eyes absent (Eya) that have been implicated in the insect developmental processes (Trivedi & Starz‐Gaiano ). The human homologs for Et, Ken, E (Bx), and Eya are glycoprotein 130 (GP130), B cell CLL/Lymphoma 6 (BCL6), Bromodomain PHD finger transcription factor (BPTF), and Eyes absent 2 (Eya2) that lead to melanoma/prostate cancer (Shariat et al .…”
Section: Regulators Of Jak/stat Signalingmentioning
confidence: 99%
“…). Many parallels have been identified between human and Drosophila JAK/STAT signaling, including neoplastic growth in JAK‐mutated flies (Trivedi & Starz‐Gaiano ). The core components of the JAK/STAT signaling pathway in Drosophila appear to be restricted and less redundant in comparison to human JAK/STAT components.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the direct control of cytokines, such as interleukins, interferons, and growth factors, the JAK/STAT pathway is central to cancer and inflammatory diseases (Banerjee et al 2017;Groner & von Manstein 2017;Yan et al 2016). Many parallels have been identified between human and Drosophila JAK/STAT signaling, including neoplastic growth in JAK-mutated flies (Trivedi & Starz-Gaiano 2018). The core components of the JAK/STAT signaling pathway in Drosophila appear to be restricted and less redundant in comparison to human JAK/STAT components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation